The university to the XXI century: the perspectives of Brazilian Educators - Lima, Paulo Gomes; Castro, Franciana; Carvalho, Maria Aparecida Vivan de (Paidéia (Ribeirão Preto), 2000)
The main concern of this study is, through the reflection, to be able to point to possible contributions to our universities that are facing the inevitable globalization; it is assumed that it is important to have good instruments to actively participate in the formation and transformation of men and women. To accomplish this, the paper deals with the theme analyzing the genesis of the University, drawing the picture of the present moment and giving the desired perspectives for the next millennium; data were collected to base the analysis of these problems and the solutions proposed, taking into account the emergent XXI Century.